Japan’s New Competitive Advantage: Enterprises’ Innovative Initiatives and Government’s Reforms - Młodawska, Jolanta (Comparative Economic Research. Central and Eastern Europe, 2011)
This article is a continuation of the report "Japan’s new competitive advantage. Arguments and proposals for structural reorientation" published in the "Comparative Economic Research for Central & Eastern Europe", vol. 13, no 1/2/2010, which mainly dealt with the role of the private sector’s cooperation with governmental agencies. The discussion presented below is divided into four sections. Section one outlines the history of new ITC firms (mobile communications, computers) after the year 2000 and addresses innovation factors. Section two characterizes Japan’s "dual economy" with respect to economic competitiveness and innovation. Section three discusses the major structural reforms (Japan Post, the Housing Loan Corporation and the Japan Highway Corporation) that were undertaken in Japan in the 21st c. Section four of the article provides final conclusions.